Results of Primary Total Hip Arthroplasty with 36-mm Femoral Heads on Highly Cross-linked Polyethylene-Minimum Seven-years Follow-up - Choi, Won-Kee (Hip Pelvis, 2014)
PURPOSE: We evaluate the clinical and radiographic midterm results of primary total hip arthroplasty (THA) using a 36 mm diameter femoral head on highly cross-linked polyethylene (minimum 7-year follow-up). MATERIALS AND METHODS: We retrospectively reviewed 73 patients (74 hips) that underwent primary THA with a 36 mm diameter femoral head on highly cross-linked polyethylene between July 2004 and February 2007. Clinical follow-ups included specific measurements like modified Harris hip scores (HHS) and Merle d'Aubigne and Postel score. For radiologic evaluations, together with position of acetabular cup at 6 weeks later of post-operation, we separately calculated the penentrations of femoral heads into polyethylene liners during post-operation and one year later check-ups, and during one year later check-ups and final check-ups. RESULTS: There were no complications except for one case of dislocation. Average modified HHS at final follow-up was 88±7.5 (range, 81-96), and Merle d'Aubigne and Postel scores were more than 15 (range, 15-18). Mean acetabular cup inclination and anteversion were 50.1°(range, 35°-58°) and 23.6°(range, 5°-38°), respectively. Average femoral head penetration during the first postoperative year was 0.071±0.034 mm/year, and steady-state wear rate determined using radiographs taken at one-year postoperatively and at latest follow-up was 0.051±0.022 mm/year. Average femoral head penetration during entire follow-ups was 0.058±0.013 mm/year. CONCLUSION: Primary THA with a large diameter femoral head on highly cross-linked polyethylene was found to produce the results comparable to previous in vitro laboratory hip simulation studies. And we also find out good scores in terms of patient's functionality.